Audit Quality In The Framework Of The Use Of Knowledge Management Maturity: A Proposal Model For Iraqi Work Environment - Rozhgar Khurshid Mahmood (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The study discusses the issue of audit quality as one of the core issues of concern to all parties benefiting from audit services, from the auditor himself to the parties benefiting from the financial statements. Accordingly, the study attempts to achieve some goals, including employing the intellectual framework through a presentation of contemporary literature on the dimensions of the study and represented With the quality of the audit and the maturity of knowledge management by making modest contributions to the number of study subjects to enrich the Arabic literature, the study followed the descriptive and analytical inductive approach, and reached a number of results, the most important of which are: The knowledge gap of knowledge about factors For a significant impact on the quality of auditing for the respondents (independent and governmental) auditors, it was (43%) for professional ethics, (45.4%) for auditing standards, (47.9%) to enable the auditor, (52.1%) for quality control, and ( 53.7%) for information technology, and (48.4%) for legal responsibility. The presence of moral differences at the level of knowledge about the factors affecting the quality of auditing for the auditors emphasizes the importance of focusing on them according to their impact on the maturity of knowledge of the auditor.